2021
DOI: 10.1136/tobaccocontrol-2020-056321
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical flavour ban and intention to vape among vape shop customers: the role of flavour preference and e-cigarette dependence

Abstract: IntroductionE-cigarette users typically initiate vaping with flavoured e-liquids. People who vape flavours tend to underestimate the harm of vaping. We examined the inter-relationship between flavour preference, vaping for cessation purposes, e-cigarette dependence, e-cigarette harm perception and purchase/use intention, given a hypothetical flavour ban. We hypothesised that non-tobacco flavour preference and vaping for cessation would be negatively associated with harm perception of e-cigarettes and intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…In the current study, non-tobacco or non-menthol/mint e-cigarette users had higher ratings for the new flavours as vaping cessation transition cluster compared with tobacco or menthol/mint flavoured e-cigarette users. This is similar to findings from a study examining responses to a hypothetical e-cigarette flavour ban among e-cigarette users recruited from vape shops in California in which non-tobacco flavoured e-cigarette users were less likely to report planning to continue e-cigarette use after a flavour ban 37. Additionally, those who reported e-cigarette use for smoking cessation reported they would be more likely to continue e-cigarette use with tobacco-only flavours if all non-tobacco flavoured e-cigarettes were banned 37.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the current study, non-tobacco or non-menthol/mint e-cigarette users had higher ratings for the new flavours as vaping cessation transition cluster compared with tobacco or menthol/mint flavoured e-cigarette users. This is similar to findings from a study examining responses to a hypothetical e-cigarette flavour ban among e-cigarette users recruited from vape shops in California in which non-tobacco flavoured e-cigarette users were less likely to report planning to continue e-cigarette use after a flavour ban 37. Additionally, those who reported e-cigarette use for smoking cessation reported they would be more likely to continue e-cigarette use with tobacco-only flavours if all non-tobacco flavoured e-cigarettes were banned 37.…”
Section: Discussionsupporting
confidence: 80%
“…This is similar to findings from a study examining responses to a hypothetical e-cigarette flavour ban among e-cigarette users recruited from vape shops in California in which non-tobacco flavoured e-cigarette users were less likely to report planning to continue e-cigarette use after a flavour ban. 37 Additionally, those who reported e-cigarette use for smoking cessation reported they would be more likely to continue e-cigarette use with tobacco-only flavours if all non-tobacco flavoured e-cigarettes were banned. 37 These data in combination with the findings displayed in figure 2 of the current study that demonstrate greater acceptability of a flavour-limiting policy among tobacco or menthol/mint flavoured e-cigarette users have important implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the impact ESRs and flavoured ESRs among users and non-users of e-cigarettes may depend on their cigarette smoking history. Previous research has shown that ESR’s hypothetical impact on adults’ e-cigarette use behaviour change may largely depend on their cigarette smoking behaviour 18 19. Specifically, adult e-cigarette users who also smoke cigarettes may be less likely to be influenced by ESR policies than e-cigarette users who are non-smokers 18 19.…”
Section: Introductionmentioning
confidence: 99%
“…21 To solve this issue while determining the relationship between the proposed factors, multilevel structural equation modeling (MSEM) is the best choice. 22 Currently, MSEM has been used in the fields of public health policy [23][24][25] and adolescent health, 26,27 but rarely in health technology use.…”
Section: Introductionmentioning
confidence: 99%